Policing performance: Performance measurement and institutional logics in law enforcement - Ranta, Valtteri (My University, 2025)
Performance measurement systems (PMS) have become central features in public-sector governance, driven by New Public Management (NPM) reforms that introduced private-sector-inspired management practices. In professionalized public sector organizations such as the police, professional discretion, public trust and situational judgement are critical. Performance measures often do not capture the complexity of frontline work in such settings, and risk generating dysfunctional motivational and behavioural outcomes due to their flawed design assumptions and usage. The Finnish police operate under an extensive performance management system, which includes an individual performance-pay structure. This thesis examines how police officers perceive the relevance of PMS and reward structures in their work. The study addresses the question through three perspectives: the level of alignment between the officers’ and PMS conceptions of good performance; the influence of PMS on task-prioritization and decision-making; and the motivational effects of the PMS-linked performance-pay system. A qualitative case-study approach is adopted, drawing on semi-structured interviews from the field operations and criminal investigation functions. The analysis is guided by the theoretical lens of institutional logics to examine how different value systems coexist in policing and shape the interpretations and enactment of PMS. The study finds that PMS are only weakly relevant to frontline policing. Officers do not perceive PMS as capturing the core aspects of their work. PMS also exert little direct behavioral influence, as they are regularly overruled by the more rigid control levers of legal imperatives and workload pressures. Performance pay is seen as misaligned with the nature of the work while intrinsic motivation takes priority. The reward system plays a marginal and largely symbolic role. Together, the findings illustrate how the more traditional professional and administrative logics of policing buffer the economic rationality represented by PMS, diminishing both intended and unintended effects. The thesis contributes to literature by providing new insight into how institutional mechanisms shape PMS enactment and consequences in a professionalized public sector organization.

Suoritusmittausjärjestelmät ovat vakiintuneet keskeiseksi osaksi julkisen sektorin tulosohjausta, johon on vaikuttanut uuden julkisjohtamisen (New Public Management, NPM) mukaiset, yksityiseltä sektorilta tuttuja johtamismalleja tuoneet uudistukset. Poliisin kaltaisissa julkisen sektorin asiantuntijaorganisaatioissa ammatillinen harkinta, julkinen luottamus ja tilannekohtainen päätöksenteko ovat keskeisiä piirteitä. Tulosmittarit eivät usein vastaa työn monimuotoisuutta, mikä voi johtaa epätoivottuihin vaikutuksiin suoritusmittausjärjestelmien virheellisen suunnittelun tai käytön seurauksena. Suomen poliisi toimii laajan tulosohjausjärjestelmän piirissä, johon sisältyy myös henkilökohtainen tulospalkkausmalli. Tämä tutkielma tarkastelee, kuinka poliisit kokevat suoritusmittausjärjestelmien ja suorituspalkkauksen merkityksen työssään. Tutkimuskysymys sisältää kolme näkökulmaa: Suoritusmittausjärjestelmien ja poliisien itsensä käsitykset hyvästä suoriutumisesta ja niiden yhdenmukaisuus; suoritusmittauksen vaikutus työtehtävien priorisointiin ja päätöksentekoon; sekä suorituspalkkausjärjestelmän motivoivat vaikutukset. Tutkimus toteutettiin laadullisena tapaustutkimuksena, keräten teemahaastatteluja valvonta- ja hälytyssektorilla sekä rikostorjunnassa työskentelevien poliisien kanssa. Analyysi pohjautuu institutionaalisten logiikkojen viitekehykseen, jonka mukaisesti tarkastellaan, kuinka erilaiset arvo- ja toimintalogiikat muovaavat suoritusmittauksen tulkintaa ja toteutumista. Löydökset osoittavat, että suoritusmittauksen merkitys poliisin operatiivisessa työssä on vähäistä. Poliisit eivät koe järjestelmien kuvastavan työn keskeisiä piirteitä. Suoritusmittausjärjestelmillä on myös heikko vaikutus käyttäytymiseen, sillä ne joutuvat joustamaan voimakkaampien ohjausvipujen, kuten oikeudellisten velvotteiden ja työkuorman hallinnan edessä. Tulospalkkaus koetaan ristiriitaiseksi sisäisen motivaation ja työn luonteen kanssa, ja suorituspalkkausosalla koetaan myös olevan rajattu, pitkälti symbolinen merkitys. Kokonaisuudessaan tulokset osoittavat, että perinteisemmät ammatilliset ja hallinnolliset logiikat vaimentavat sekä suoritusmittauksen toivottuja että epätoivottuja vaikutuksia. Tutkimus tuo kirjallisuuteen uutta ymmärrystä, kuinka institutionaaliset mekanismit muovaavat suoritusmittausten toteutumista julkisen sektorin asiantuntijatyössä.
Keywords: performance management, performance measurement, PMS, performance pay, police, policing, public sector, New Public Management, NPM, dysfunctional consequences, institutional logics, tulosohjaus, suoritusmittaus, tulospalkkaus, suorituspalkkaus, poliisi, julkinen sektori, uusi julkisjohtaminen, NPM, institutionaaliset logiikat